(untitled) (Research, Society and Development, 2020)
This study aimed to evaluate the ice cream crystal content considering the addition of enzymes lactase (0.3% to 0.9%) and transglutaminase (0.6% to 7.4%), employing different incubation temperatures (13 to 47 °C) through a 23 central composite rotatable design (DCCR). The crystals content was estimated by ice cream scattering in blades and the crystals images were obtained with a bright field optical microscope for counting and determining the crystals size using Image J software. All ice cream treatments prepared at 40 oC (T2, T6, and T8) and TA2 treatment (T2 treatment similar formulation) showed small content of crystals if compared with the temperatures of 20 and 30 ºC; it was probably associated with a large presence of air bubbles, fat globules and probably some casein micelles, making them ideal for small crystals agglomeration that form a firmer, smooth and cohesive texture. Moreover, the combined use of lactase and transglutaminase enzymes in the ice cream is viable, efficient and an easy technology for ice cream production. Furthermore, the use of response surface methodology was effective in selecting the best formulation in relation to desirability features ensuring its use in the ice cream development.